Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1002/nme.5570
|View full text |Cite
|
Sign up to set email alerts
|

The Discontinuity‐Enriched Finite Element Method

Abstract: Summary We introduce a new methodology for modeling problems with both weak and strong discontinuities independently of the finite element discretization. At variance with the eXtended/Generalized Finite Element Method (X/GFEM), the new method, named the Discontinuity‐Enriched Finite Element Method (DE‐FEM), adds enriched degrees of freedom only to nodes created at the intersection between a discontinuity and edges of elements in the mesh. Although general, the method is demonstrated in the context of fracture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
59
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 56 publications
(61 citation statements)
references
References 33 publications
0
59
0
Order By: Relevance
“…59 By contrast, the second is to adjust the approximation of the primary variable to let it satisfy the Dirichlet boundary condition exactly, for example, the one proposed by Zheng et al 60 for the element-free Galerkin method and another approach proposed by van den Boom et al 61 for the discontinuity-enriched FEM. 62,63 The Nitsche method 58 has received substantial attention recently and has been applied to the meshfree method 64,65 and the partition-of-unity methods. [66][67][68][69][70][71] It is appealing since it results in a variational consistent single-field formulation, positive-definite stiffness matrix, and optimal convergence.…”
Section: Introductionmentioning
confidence: 99%
“…59 By contrast, the second is to adjust the approximation of the primary variable to let it satisfy the Dirichlet boundary condition exactly, for example, the one proposed by Zheng et al 60 for the element-free Galerkin method and another approach proposed by van den Boom et al 61 for the discontinuity-enriched FEM. 62,63 The Nitsche method 58 has received substantial attention recently and has been applied to the meshfree method 64,65 and the partition-of-unity methods. [66][67][68][69][70][71] It is appealing since it results in a variational consistent single-field formulation, positive-definite stiffness matrix, and optimal convergence.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, enrichment functions are exactly zero at original mesh nodes. Therefore, original mesh nodes retain their physical meaning and essential boundary conditions can be enforced directly on non-matching edges (Cuba-Ramos et al 2015;Aragón and Simone 2017;van den Boom et al 2019a). It was shown that IGFEM is optimally convergent under mesh refinement for problems without singularities (Soghrati et al 2012a, b).…”
Section: Introductionmentioning
confidence: 99%
“…IGFEM was later developed into the Hierarchical Interface-enriched Finite Element Method (HIFEM) (Soghrati 2014) that allows for intersecting discontinuities, and into the Discontinuity-Enriched Finite Element Method (DE-FEM) (Aragón and Simone 2017), which provides a unified formulation for both strong and weak discontinuities (i.e., discontinuities in the field and its gradient, respectively). DE-FEM, which inherits the same advantages of IGFEM over X/GFEM, has successfully been applied to problems in fracture mechanics (Aragón and Simone 2017;Zhang et al 2019a) and fictitious domain or immersed boundary problems with strongly enforced essential boundary conditions (van den Boom et al 2019a). A drawback of IGFEM is that quadratic enrichment functions are needed when the method is applied to background meshes composed of bilinear quadrangular elements (Aragón et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…For the next hierarchy level, only the coordinate x 4 is located on Γ i , but here, both weak ( α ) and strong ( β ) DOFs are present. Because β physically represents the crack opening displacement, their values are readily available once the jump in the displacement is known, ie, bold-italicβ21=bold-italicufalse(bold-italicx4false)=truebold-italicufalse(bold-italicx4false)false|normalΓnormalc+truebold-italicufalse(bold-italicx4false)false|normalΓnormalc. Then, solving for α at x 4 follows the same procedure just described for α 11 and α 12 .…”
Section: Formulationmentioning
confidence: 99%
“…Cuba‐Ramos et al demonstrated IGFEM as an immersed boundary method, by using Lagrange multipliers to weakly impose Dirichlet boundary conditions on non‐matching boundaries. More recently, Aragón and Simone introduced the Discontinuity‐Enriched FEM (DE‐FEM) as a generalization of IGFEM to treat both weak and strong discontinuities with a unified formulation. In addition to the flexibility of dealing with both discontinuity types, DE‐FEM inherits all of the virtues of IGFEM/HIFEM: The construction of both weak and strong enrichment functions is straightforward, as they are based on the standard Lagrange shape functions of integration elements; Because enrichment functions vanish at original mesh nodes, the Kronecker‐delta property is maintained in standard nodes, allowing essential boundary conditions to be applied in the same way as in standard FEM; With the use of a diagonal preconditioner, or a proper scaling factor for the enrichment functions, the formulation used for treating weak discontinuities is stable, ie, the condition number increases at the same rate as that of standard FEM under mesh refinement; A hierarchical implementation of DE‐FEM can analyze multiple discontinuities and n ‐junctions within a single element.…”
Section: Introductionmentioning
confidence: 99%